Peran Humas Sekretariat DPRD Provinsi Kalimantan tengah dalam Pengelolaan Aspirasi Masyarakat - Arja Kiannur; Muhammad Saifullah; Anggi Windiarty; Tiya Silviya; Novita Mayasari Angelia (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2025)
The management of public aspirations is a strategic task of the Public Relations (PR) department at the DPRD Secretariat to support information transparency and public participation. This study aims to examine the roles, challenges, and strategies of PR in managing public aspirations in Central Kalimantan Province. Using empirical and normative juridical approaches, primary and secondary data were qualitatively analyzed to evaluate the effectiveness of communication mechanisms implemented. The findings indicate that PR serves as a mediator between the public and the DPRD through hearings, discussion forums, and digital platforms. In addition to gathering public aspirations, PR also educates the public on mechanisms for submitting opinions and the importance of public participation. However, this study identifies several challenges, such as limited access to information for remote communities, insufficient public understanding of aspiration submission procedures, and slow responses to incoming inputs. To address these issues, innovations are required, including the implementation of an online-based management information system, capacity building through training, and periodic evaluations of aspiration management processes. These strategies are expected to enhance transparency, accountability, and the effectiveness of aspiration management, ensuring that public aspirations are optimally accommodated in legislative processes and regional development planning.